Development and Validation of the Subjective Occupational Aspiration Scale Using a Rasch Model Approach. (December 2019) - Han, Hyojung; Rojewski, Jay W.; Kwak, Minho
This study proposes and measures a new construct, subjective occupational aspiration, that refers to individuals' preferences for selected aspects of occupations—economic rewards, authority, freedom, education required, and ability required—that, collectively, support the expression of those occupations. Using a four-step approach to constructing psychometric instruments based on the Rasch model, this study developed and validated the Subjective Occupational Aspiration Scale (SOAS). The SOAS consists of 24 4-point Likert-type items. Both infit and outfit statistics indicated that the Rasch model predicted both items and persons within a reasonable error bound, validating all initial 24 items of the SOAS. However, two sets of items showed reversed difficulties. The final instrument that reflects the corrected difficulty order of items is provided. Suggestions and implications for using the SOAS in practice are also discussed.